IMPLIKASI PERUBAHAN PT. JAMSOSTEK (PERSERO) MENJADI BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) TERHADAP JAMINAN SOSIAL KETENAGAKERJAAN DI INDONESIA - Suzanalisa Suzanalisa (Universitas Batanghari Jambi, 2015)
This study aims to identify and analyze changes PT. Jamsostek (persero) into BPJS Ketenagakerjaan in realizing social security in indonesia and the implications of changes in PT. Jamsostek (persero) into BPJS Ketenagakerjaan for social security employment in indonesia. This study uses normative juridical research method using the conceptual approach and the approach of legislation later interpretation, judging and evaluation of all policies in the framework of the legal implications of social security as a result of changes in employment in indonesia PT. Jamsostek (persero) into BPJS Ketenagakerjaan. The study results obtained changes in PT. Jamsostek (persero) into BPJS Ketenagakerjaan in realizing social security in indonesia has a positive impact on employment embodiment of social security in indonesia by virtue of law no. 24 of 2011 on the social security agency, among others: changes in the organization of soes became a legal entity of public law entities; changes in the financial treatment in organizing body both in terms of the separation of assets, entities organizers and participants as well as financial reporting system is directly responsible to the president; changes in the coverage required in the protection provided by BPJS Ketenagakerjaan of the formal labor protection for all labor and implications change PT. Jamsostek (persero) into BPJS Ketenagakerjaan for social security employment in indonesia provide adequate protection and is absolutely needed by all workers in indonesia in everyday life, including his family and for the country with the social security embodied accumulation of funds, involving the entire state and are thus becoming a national national savings and strengthen national resilience derived from the pooled fund managed by BPJS.Keywords: Implications, Change, Social Security Employment